A Decline in Intraoperative Renal Near-Infrared Spectroscopy Is Associated With Adverse Outcomes in Children Following Cardiac Surgery. Issue 4 (April 2016) - Gist, Katja M.; Kaufman, Jonathan; da Cruz, Eduardo M.; Friesen, Robert H.; Crumback, Sheri L.; Linders, Megan; Edelstein, Charles; Altmann, Christopher; Palmer, Claire; Jalal, Diana; Faubel, Sarah
Abstract : Objectives: Renal near-infrared spectroscopy is known to be predictive of acute kidney injury in children following cardiac surgery using a series of complex equations and area under the curve. This study was performed to determine if a greater than or equal to 20% reduction in renal near-infrared spectroscopy for 20 consecutive minutes intraoperatively or within the first 24 postoperative hours is associated with 1) acute kidney injury, 2) increased acute kidney injury biomarkers, or 3) other adverse clinical outcomes in children following cardiac surgery. Design: Prospective single center observational study. Setting: Pediatric cardiac ICU. Patients: Children less than or equal to age 4 years who underwent cardiac surgery with the use of cardiopulmonary bypass during the study period (June 2011–July 2012). Interventions: None. Measurements and Main Results: A reduction in near-infrared spectroscopy was not associated with acute kidney injury. Nine of 12 patients (75%) with a reduction in renal near-infrared spectroscopy did not develop acute kidney injury. The remaining three patients had mild acute kidney injury (pediatric Risk, Injury, Failure, Loss, End stage-Risk). A reduction in renal near-infrared spectroscopy was associated with the following adverse clinical outcomes: 1) a longer duration of mechanical ventilation ( p = 0.05), 2) longer intensive care length of stay ( p = 0.05), and 3) longer hospital length of stay ( p < 0.01). A decline in renal near-infrared spectroscopy in combination with an increase in serum interleukin-6 and serum interleukin-8 was associated with a longer intensive care length of stay, and the addition of urine interleukin-18 to this was associated with a longer hospital length of stay. Conclusions: In this cohort, the rate of acute kidney injury was much lower than anticipated thereby limiting the evaluation of a reduction in renal near-infrared spectroscopy as a predictor of acute kidney injury. A greater than or equal to 20% reduction in renal near-infrared spectroscopy was significantly associated with adverse outcomes in children following cardiac surgery. The addition of specific biomarkers to the model was predictive of worse outcomes in these patients. Thus, real-time evaluation of renal near-infrared spectroscopy using the specific levels of change of a 20% reduction for 20 minutes may be useful in predicting prolonged mechanical ventilation and other adverse outcomes in children undergoing cardiac surgery.